2006
DOI: 10.1160/th06-01-0007
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic activity is associated with the anatomical as well as the functional severity of peripheral arterial occlusive disease

Abstract: The importance of prothrombotic activity in cardiovascular disease has been well established. However, limited data exist on the relationship between prothrombotic activity and the severity of peripheral arterial occlusive disease (PAD). The objective of the present study was to investigate the relationship between markers of haemostasis and the diagnostic measures of PAD: ankle-brachial-index (ABI), maximum treadmill walking distance and angiographic score. In a cross-sectional study of 127 patients (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 37 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…18 PPACK-NP treatment significantly reduced serum thrombin-antithrombin (TAT) complexes (5.43 ± 0.64 ng/ml, N=5; p=0.0001 vs. saline, p=0.032 vs control NP) (Fig. 5A) versus saline (13.32 ± 1.01 ng/ml, N=6) and control NP (9.96 ± 1.64 ng/ml, N=5, p=NS vs. saline).…”
Section: Resultsmentioning
confidence: 99%
“…18 PPACK-NP treatment significantly reduced serum thrombin-antithrombin (TAT) complexes (5.43 ± 0.64 ng/ml, N=5; p=0.0001 vs. saline, p=0.032 vs control NP) (Fig. 5A) versus saline (13.32 ± 1.01 ng/ml, N=6) and control NP (9.96 ± 1.64 ng/ml, N=5, p=NS vs. saline).…”
Section: Resultsmentioning
confidence: 99%
“…In the clinical field, the evidence is inconsistent; some cross-sectional studies have shown a positive association between thrombin generation and aortic, carotid, and peripheral arterial atherosclerosis [1517], whereas others have not [1820]. …”
Section: Introductionmentioning
confidence: 99%